Does the CEO's Entrenchment Affect the Financial Communication Quality? Empirical Evidence from France - Dhouha Bouaziz (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- What is the impact of the CEO's entrenchment on the financial communication quality in the French context? Motivation- In fact, it is important to study the different characteristics of the CEO, which can facilitate the entrenchment and their effect on the quality of financial communication in the French context. Idea- The purpose of this paper is to investigate the impact of the CEO's entrenchment on the financial communication quality examined by the discretionary accruals. Data- Our sample is made up of 335 companies listed on the CAC All Tradable index for the period from 2011 to 2020. However, we have excluded some financial companies due to their atypical behavior in financial reporting, firms with insufficient annual reports and firms with insufficient data about the CEO's entrenchment. Therefore, the final number of firms used in this study was 151 over ten years, producing a total of 1510 firm-year observations. Tools- Our regressions will be estimated by the feasible generalized least squares (FGLS) method. Findings- Using the discretionary accruals, as a proxy for the earnings management, we obtained results from the Kothari et al. (2005) model, which indicates that there is a significant positive relationship between the CEO's duality, ownership and the quality of financial communication, while there is no significant relationship between the CEO's turnover and the financial communication quality. Contribution- This research is a contribution to the literature by demonstrating how the CEOs' entrenchment enables them to manipulate the accounting results to improve their financial situation.
Keywords: M41; M42; M48; 650; CEO's entrenchment; earnings management (EM); financial communication quality; CEO's ownership